Narrative coherence in multiple forensic interviews with child witnesses alleging physical and sexual abuse. Issue 5 (29th April 2020) - Szojka, Zsofia A.; Nicol, Annabelle; La Rooy, David
Summary: This study investigated the narrative coherence of children's accounts elicited in multiple forensic interviews. Transcriptions of 56 police interviews with 28 children aged 3–14 years alleging physical and sexual abuse were coded for markers of completeness, consistency and connectedness. We found that multiple interviews increased the completeness of children's testimony, containing on average almost twice as much new information as single interviews, including crucial location, time and abuse‐related details. When both contradictions within the same interview and across interviews were considered, contradictions were not more frequent in multiple interviews. The frequency of linguistic markers of connectedness remained stable across interviews. Multiple interviews increase the narrative coherence of children's testimony through increasing their completeness without necessarily introducing contradictions or decreasing causal‐temporal connections between details. However, as 'ground truth' is not known in field studies, further investigation of the relationship between the narrative coherence and accuracy of testimonies is required.